48-3(x-4)=3x

Simple and best practice solution for 48-3(x-4)=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48-3(x-4)=3x equation:


Simplifying
48 + -3(x + -4) = 3x

Reorder the terms:
48 + -3(-4 + x) = 3x
48 + (-4 * -3 + x * -3) = 3x
48 + (12 + -3x) = 3x

Combine like terms: 48 + 12 = 60
60 + -3x = 3x

Solving
60 + -3x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
60 + -3x + -3x = 3x + -3x

Combine like terms: -3x + -3x = -6x
60 + -6x = 3x + -3x

Combine like terms: 3x + -3x = 0
60 + -6x = 0

Add '-60' to each side of the equation.
60 + -60 + -6x = 0 + -60

Combine like terms: 60 + -60 = 0
0 + -6x = 0 + -60
-6x = 0 + -60

Combine like terms: 0 + -60 = -60
-6x = -60

Divide each side by '-6'.
x = 10

Simplifying
x = 10

See similar equations:

| 2x^3-32x= | | 8b=104 | | 23x+-1+45x=135 | | -3x-2(9+5x)=18-5(2x-5) | | 2y+8(5000-y)=44y | | 3x=5x-22 | | 12+7x=-2 | | 6m-11=12+22 | | 3(y-1)-3y=3(y-6) | | 256x^2+32x+1=0 | | x^2-18x+16=0 | | 12d+5=7 | | 7x-12=-2 | | .5+17+n=20 | | -x-(13+14)=-3(5-9x)+2 | | r^2+8r=-15 | | 5x^2+80x+230=0 | | x^2-16*x+5= | | y^4+2y^2-3=0 | | 3t^2+2=9t^4 | | 6(3x-1)=25 | | 3*2-(1/5)*3+5= | | 3x-4=5x-26 | | 4(2y-8)=10y-20 | | 14/1=z/2 | | x^2-20x+83=0 | | 10x^2-x+9=0 | | 20(p^2-1)=9p | | 3x-5=x+27 | | 9n-5=8n | | 54-4x=2x-36 | | .83-.25=a |

Equations solver categories